Pharmacology / Humphrey P. Rang ... [et al.]. - Rang, H. P. (Churchill Livingstone, 2003)
Providing students with an overview of how a class of drugs will be used in a clinical situation, this text covers physiology and biochemistry as well as pharmacology. It explains how drugs act and relates them to their effects and clinical uses.